MyoD regulates apoptosis of myoblasts through microRNA-mediated down-regulation of Pax3 - Hirai, Hiroyuki (The Rockefeller University Press, 2010)
The molecules that regulate the apoptosis cascade are also involved in differentiation and syncytial fusion in skeletal muscle. MyoD is a myogenic transcription factor that plays essential roles in muscle differentiation. We noticed that MyoD(−/−) myoblasts display remarkable resistance to apoptosis by down-regulation of miR-1 (microRNA-1) and miR-206 and by up-regulation of Pax3. This resulted in transcriptional activation of antiapoptotic factors Bcl-2 and Bcl-xL. Forced MyoD expression induces up-regulation of miR-1 and miR-206 and down-regulation of Pax3, Bcl-2, and Bcl-xL along with increased apoptosis in MyoD(−/−) myoblasts. In contrast, MyoD gene knockdown increases cell survival of wild-type myoblasts. The 3′ untranslated region of Pax3 mRNA contains two conserved miR-1/miR-206–binding sites, which are required for targeting of these microRNAs (miRNAs). Therefore, these data suggest that MyoD not only regulates terminal differentiation but also apoptosis through miRNA-mediated down-regulation of Pax3. Finally, MyoD, miR-1, and miR-206 are all down-regulated in quiescent satellite cells, which may be required for maintenance of muscle stem cells.